Technique of Tibial Tuberosity Transposition and Advancement (TTTA) With Use of TTA-Maquet Cage-Only in Dog - Dornas, Fellipe Pio; dos Santos Malta, Caio Afonso; Lopes Muzzi, Leonardo Augusto; Ribeiro, Daniel Oliveira; Pacheco, Larissa Teixeira; Ferreira Telles, Tamara Suzuki; Perez Neto, Daniel Munhoz; Lázaro Muzzi, Ruthnéa Aparecida (Acta Scientiae Veterinariae, 2019)
Background: The most common conditions that compromise the stifle joint in dogs are medial patellar luxation (MPL) and cranial cruciate ligament (CCL) rupture. Surgical procedures are usually indicated for the treatment of these diseases. One ordinary technique for the treatment of MPL is the tibial tuberosity transposition, and one prominent technique for CCL rupture is the tibial tuberosity advancement. These techniques can be associated in one surgical procedure called tibial tuberosity transposition and advancement (TTTA) for the simultaneous treatment of both stifle diseases. The aim of this study is to report the surgical treatment of a dog with MPL and CCL rupture affecting the same joint by the TTTA technique with the use of a TTA-Maquet cage-only. Case: A 3-year-old Pitbull dog weighing 39 kg was attended at Veterinary Hospital with a history of marked lameness in the left pelvic limb. The orthopedic examination showed positive results for cranial drawer motion and tibial compression tests, and a complete CCL rupture was diagnosed. The presence of patellar luxation was evaluated by manual pressure on the patella, and grade 3 of MPL was diagnosed. Both conditions were affecting the same stifle joint. In addition, survey radiographs of the affected joint were performed. Surgical treatment was indicated by the TTTA technique. Radiographic measurements were taken to calculate the cranial tibial tuberosity advancement by the tibial plateau and the common tangent methods, and a titanium TTA-Maquet cage-only of 10.5 x 20.0 mm was selected. Linear osteotomy was performed on the tibial tuberosity with the aid of an oscillating saw, based on the Maquet hole technique. The tibial tuberosity was carefully displaced cranially and the cage was inserted at the site of osteotomy. The cage ears were molded on the tibial surface and fixed with 2.4 mm self-tapping cortical screws. At the moment of the cage attachment to the tibial tuberosity, orthopedic washers of 2 mm wide were placed between the cranial ears of the cage and the tibial tuberosity, thus promoting a lateral transposition of the tibial tuberosity. The patient was maintained in the early postoperative period with Robert Jones bandage, and with antibiotic, analgesic and anti-inflammatory drugs. On the second day after the procedure partial limb support with presence of mild lameness was observed. At three months postoperatively, the animal had no claudication and MPL was corrected. The radiographic examination showed the proper process of bone repair at the osteotomy site. In the clinical evaluation performed at one year after surgery the patient was in good condition without lameness and with proper limb support and muscular gain. Discussion: The studies that evaluated the association of tibial tuberosity transposition and tibial tuberosity advancement techniques (TTTA) for the simultaneous treatment of MPL and CCL rupture demonstrated that this is a viable and effective procedure. In this report, the accomplishment of tibial osteotomy based on the Maquet hole and the advancement of the tibial tuberosity with the TTA-Maquet cage-only allowed the dynamic stabilization of the CCL deficient stifle and the early use of the affected limb. In addition, the TTTA technique proved to be effective for the correction of grade 3 of MPL in a large dog, allowing adequate recovery of the limb function without complications during a one year evaluation period.